Rhinoplasty: The Asymmetric Crooked Nose—An Overview - Kosins, Aaron M.; Daniel, Rollin K.; Nguyen, Dananh P. (Facial Plastic Surgery, 2016)
There are three reasons why the asymmetric crooked nose is one of the greatest challenges in rhinoplasty surgery. First, the complexity of the problem is not appreciated by the patient nor understood by the surgeon. Patients often see the obvious deviation of the nose, but not the distinct differences between the right and left sides. Surgeons fail to understand and to emphasize to the patient that each component of the nose is asymmetric. Second, these deformities can be improved, but rarely made flawless. For this reason, patients are told that the result will be all “–er words,” better, straighter, cuter, but no “t-words,” there is no perfect nor straight. Most surgeons fail to realize that these cases represent asymmetric noses on asymmetric faces with the variable of ipsilateral and contralateral deviations. Third, these cases demand a wide range of sophisticated surgical techniques, some of which have a minimal margin of error. This article offers an in-depth look at analysis, preoperative planning, and surgical techniques available for dealing with the asymmetric crooked nose.
Keywords: crooked nose; rhinoplasty; septoplasty; asymmetric nose; osteotomies